Barriers to Federal Funding for Underserved Communities: Legal and Policy Perspective - Foster, Nicholas L (International Journal of Scientific Research and Management (IJSRM), 2023)
Social advancement together with economic growth in underserved areas requires proper acquisition of federal funding. However, numerous legal and policy barriers impede equitable access to these financial resources. This assessment reveals how complex project mandates and limited qualification boundaries create discrimination walls at institutional levels that increase regulatory problems for funding access by disadvantaged groups. The piece gives multiple political suggestions to simplify money requests but also offers technical help for distribution of funds in proportionate amounts while maintaining financial transparency. Building a funding structure that combines both inclusiveness and fairness requires complete solutions for known obstacles to ensure economic development accessibility by all communities.Historic systemic disadvantages maintain their obstacles for particular groups because these groups struggle to secure funding within federal programs. Poor resource awareness combined with bureaucratic red tape together with the lack of community members in decision-making teams increase these barriers even more. Federal legislation needs express changes which would enable the development of streamlined grant applications and simplified regulatory needs along with funding mechanisms designed to support disadvantaged communities before other programs. The increased accountability of institutions with local agency support between federal and local organizations will create better funding access for all social groups.